Amangeldin M., Kenzhebayeva S., Bikebayeva A., Maidanova B. Structure analysis of the worldwide pharmaceutical market and prospects for its development in Kazakhstan: Al-Farabi Kazakh National University, Kazakhstan, Almaty; 2 - Xinjiang institute of medicine, China, Urumqi - Yessimsiitova Z., Ablaikhanova N.,, Alimova S., Baishanbo A., (Eurasian Journal of Ecology, 2018)
Over recent years, special attention has been paid to medicinal plants, and the number of those wishing to prepare medicinal herbs has increased, which are used for the preparation of medicine raw materials in traditional and modern medicine. Nowadays more people are beginning to take care of their health, lead a healthy lifestyle, proper nutrition and treatment for chronic diseases with medicinal plants, since they are less toxic to chemicals, more natural to the body and more suitable for long-term use. In the literature review of the article, based on the literature data, the useful and medicinal properties of the Frángula álnus plant are shown. In the leaves, bark, fruits and buds of buckthorn fragile in large quantities, anti-glycoside are identified, which determine the main basic pharmacological effect of this unusual plant. In non-traditional medicine, Frángula álnus is using for gastritis, gastric ulcer and duodenal ulcer, liver disease, heart failure, persistent cough, rheumatism and radiculitis, skin diseases. Also noted in a number of cases, the therapeutic effect of the drug is determined not only by the main active substance, but also by the whole set of mineral salts and trace elements contained in it, including sugars. Key words: Frangula alnus, buckthorn, medicinal plants, medicine raw material.